An Unusual Diagnosis for an Infant Presenting with Olive-Shaped Abdominal Mass - Ghada Maher Abdulaziz; Khalid Maher Mohamed; Ayat Hassan Zilai; Asmaa Ibrahim Attieh; Eman Abdulmohsen Alhammad; Abdullah Yahya Akkam (Case Reports in Pediatrics)
A 3-month-old male infant was bought to the emergency department with almost 3 weeks of projectile, bilious emesis after each feed. On presentation, he was cachectic and severely dehydrated and had a palpable olive in the epigastric region. Hypertrophic pyloric stenosis was excluded by abdominal ultrasound. The barium meal demonstrated a massively distended stomach, absence of distal gas, and triple bubble sign. Given the radiological findings, the patient underwent an emergency exploratory laparotomy and a congenital duodenal web (CDW) was discovered. While the clinical picture suggested the diagnosis of HPS, barium meal eventually revealed congenital duodenal web. To our knowledge, no other cases of palpable olive mass as the presenting sign of proximal bowel obstruction have been published.